2021
DOI: 10.1002/ejhf.2271
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure drug titration, discontinuation, mortality and heart failure hospitalization risk: a multinational observational study (US, UK and Sweden)

Abstract: Aims Use and dosing of guideline‐directed medical therapy (GDMT) in patients with heart failure (HF) have been shown to be suboptimal. Among new users of GDMT in HF, we followed the real‐life patterns of dose titration and discontinuation of angiotensin‐converting enzyme inhibitors (ACEi), angiotensin receptor blockers (ARB), beta‐blockers, mineralocorticoid receptor antagonists (MRA) and angiotensin receptor–neprilysin inhibitors (ARNI). Methods and results New users were identified in health care databases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
133
3
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(146 citation statements)
references
References 58 publications
4
133
3
6
Order By: Relevance
“…Neurohormonal antagonists, including angiotensin-converting enzyme inhibitors (ACEi), angiotensin receptor blockers, angiotensin receptor neprilysin inhibitors, beta-blockers, and mineralocorticoid receptor antagonists, and sodiumglucose co-transporter 2 (SGLT2) inhibitors, are the mainstay of HFrEF treatment, improving the clinical course of HF. 7,[12][13][14][15][16] Adherence to GDMT is associated with improved outcome. [17][18][19][20][21][22] Data from population-based studies reported a decline in HF-related hospitalizations and mortality over the last two decades.…”
Section: Evidence-based Therapy For Heart Failure With Reduced Ejecti...mentioning
confidence: 99%
“…Neurohormonal antagonists, including angiotensin-converting enzyme inhibitors (ACEi), angiotensin receptor blockers, angiotensin receptor neprilysin inhibitors, beta-blockers, and mineralocorticoid receptor antagonists, and sodiumglucose co-transporter 2 (SGLT2) inhibitors, are the mainstay of HFrEF treatment, improving the clinical course of HF. 7,[12][13][14][15][16] Adherence to GDMT is associated with improved outcome. [17][18][19][20][21][22] Data from population-based studies reported a decline in HF-related hospitalizations and mortality over the last two decades.…”
Section: Evidence-based Therapy For Heart Failure With Reduced Ejecti...mentioning
confidence: 99%
“…A recent multinational study analysing healthcare databases from the US, UK and Sweden cements the findings of suboptimal titration, as well as high rates of premature discontinuation. [ 23 ] In patients who have been hospitalised with a recent diagnosis of HF and subsequently initiated on GDMT, after a follow-up of 12 months, target dosage rates were 15% for ACEIs, 10% for ARBs, 12% for β-blockers and 30% for ARNIs. MRAs, in contrast, reached target dose at a rate of 60%.…”
Section: International Use and Dosing Of Gdmtmentioning
confidence: 99%
“…Discontinuation rates were far higher than CHAMP-HF, reaching 55% for ACEIs, 33% for ARBs, 24% for β-blockers, 27% for ARNIs and 40% for MRAs. [ 19 , 23 ]…”
Section: International Use and Dosing Of Gdmtmentioning
confidence: 99%
“…Age is a recognised major determinant of low adherence to GDMT in HFrEF. [ 17 , 18 , 20 , 21 ] In the CHAMP-HF registry, older age was associated with the lower use of β-blockers, MRAs and angiotensin receptor–neprilysin inhibitor (ARNI), and, at the 12-month follow-up, dose maximisation was less likely with increasing age. [ 18 , 39 ] Similarly, in the US GWTG-HF registry, there was a decreasing gradient in the use of GDMT with increasing age, although the authors correctly highlighted that the prescription rate was high overall also in the oldest category (i.e.…”
Section: Adherence To Guideline-directed Medical Therapy In Older Pat...mentioning
confidence: 99%